(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The proper function of photovoltaic (PV) systems needs the design of an maximum power point tracking system (MPPT) to draw out the maximum possible power from the photovoltaic array. This paper investigates the efficiency of a neuro-fuzzy logic controller over conventional ones intended to track the maximum power point (MPP). The proposed model used for simulation studies is implemented using Matlab/Simulink. A comparison between the classical Perturb and Observe (P&O) algorithm and fuzzy algorithm in terms of MPPT accuracy is provided. Results prove that the proposed model is simple, reliable and allows simulation under different operating conditions.